LITERACY: A SEARCH FOR CORRELATES - Amare, Asgedom (The Ethiopian Journal of Education, 2024)
A Telliew of literature of dellelopment processes in Developing Nations shows that litertacy has often been associated with indicators of the process of modernization. This study attempts to examine the correlartes of literacy in the Ethiopian context. A surlley study of 200 household heads in the subdistrict of rural Bahir Dar was made to investigate the hypothesized relationship. The results suggest mixed relationships. Literacy is not necessarily, a correlate of the lIariables; technification, innollativeness, cosmopolitannes and dislocation. Economic status was found a negative correlate of literacy. Exposure to the mass media, educational aspiration, and conscientization were, however, identified as significant positive correlates.